Calculations in fundamental physics - Heddle, T. (Commonwealth and international library. Electrical engineering., 1971)
Calculations in Fundamental Physics, Volume I: Mechanics and Heat focuses on the mechanisms of heat. The manuscript first discusses motion, including parabolic, angular, and rectilinear motions, relative velocity, acceleration of gravity, and non-uniform acceleration. The book then discusses combinations of forces, such as polygons and resolution, friction, center of gravity, shearing force, and bending moment. The text looks at force and acceleration, energy and power, and machines. Considerations include momentum, horizontal or vertical motion, work and energy, pulley systems, gears and chai.